Socioeconomic Status and Health Gaps: A Baseline Study of India’s Marginalized Population - Sanyal, Mauli (Margins/Marges/Margini, 2025)
Marginality is a manifestation of ‘capability’ deprivation that affects the ‘functioning’1 of individuals. It is specific to race, ethnicity, religion, or socioeconomic background and leads to oppression and prejudice to a certain degree. Disparity in socioeconomic opportunities influences health, a prime indicator of the Human Development Index. India is a centre of marginalization, undergoing an epidemiological shift, and making slow progress towards universal health care. Under these circumstances, a detailed study of the healthcare system, with special reference to the marginal community, is worthwhile. The paper is descriptive in nature and uses secondary data from the NSSO, India, reports. The sample considered comprises people hospitalized in the last 365 days and examines disease incidence, healthcare utilization and financing patterns. The study reveals that there exist differences in morbidity pattern, access to and utilization of healthcare services, the magnitude of healthcare expenditures and insurance enrolment across socioeconomic groups. The pillars of egalitarian health care—availability, accessibility, and affordability—are gravely threatened, especially among the marginalized communities in India. The analysis is crucial in policy framing, as any anomaly between the development programs and the target groups can adversely affect the marginals and the deprived.